THE INFLUENCE OF COMPETENCE AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE AT THE DEPARTMENT OF CULTURE AND TOURISM OF DARMASRAYA REGENCY - Putra, Riyosnal; Albar, Defni; Aima, M. Havidz; Lusiana, Lusiana (Gapenas Publisher, 2025)
The purpose of this study is to determine and analyze the competence, career development, work discipline, employee performance at the Department of Culture and Tourism of Darmasraya Regency. The method and type of research used is a quantitative research type with a survey research method, data was obtained directly through questionnaires to 48 respondents who are employees at the Department of Education and Culture of Darmasraya Regency. Sampling used the total sampling technique. Data analysis was carried out in several stages, namely 1) Validity test was tested with Pearson correlation (r count > r table). 2) Reliability was tested with Cronbach Alpha (> 0.60 is considered reliable). 3) Normality test to determine whether the data is normally distributed or not 4) T test to determine the effect of each independent variable on the dependent variable. 5) F test to determine the effect of competence and career development simultaneously on employee performance. 6) Coefficient of Determination (R²) to determine how much the independent variable contributes to explaining the dependent variable. Based on the research results and discussions that have been presented above, several conclusions can be drawn as follows: 1) Competence variables affect employee performance at the Department of Culture and Tourism of Darmasraya Regency. This means that the better the Competence, the higher the level of performance will be. 2) Career Development variables have a positive effect on employee performance at the Department of Culture and Tourism of Darmasraya Regency. This means that the better the work discipline of employees in an agency, the higher the employee performance will be. 3) Simultaneously, Competence and Career Development have a positive effect on employee performance at the Department of Culture and Tourism of Darmasraya Regency.